Inclusive Classroom Management to Accommodate Diverse Student Characteristics and Learning Preferences in Indonesian Primary Education: A Qualitative Case Study - Khairiyah Khairiyah; Manap Somantri; Muhammad Kristiawan (Journal of Social Work and Science Education, 2026)
This qualitative case study examined inclusive classroom management practices accommodating diverse student characteristics and learning preferences at SD Negeri 6 Muara Rupit, a public elementary school in Indonesia. Participants included two classroom teachers, twenty-eight students, and the school principal, selected purposively. Data were collected through semi-structured interviews, non-participant classroom observations, and document analysis (lesson plans and teaching modules). The interactive model of data reduction, data display, and conclusion drawing guided data analysis. Findings revealed four main themes. First, teachers implemented systematic planning by designing varied instructional activities and flexible seating arrangements before instruction. Second, classroom implementation involved interactive strategies, including group discussions, collaborative learning, questioning sessions, and positive behavior management rather than punitive approaches. Third, classroom organization featured flexible seating rearrangements and heterogeneous grouping to facilitate peer interaction. Fourth, teachers employed adaptive strategies such as simplifying explanations, providing individual guidance, and varying instructional methods to address challenges including student diversity, limited instructional time, and constrained resources. Supporting factors included teacher competence, positive teacher-student relationships, school leadership support, and available facilities. The study concludes that inclusive classroom management extends beyond behavioral control to function as a comprehensive pedagogical framework for creating participatory, student-centered learning environments. Practical implications recommend targeted professional development in differentiated instruction, flexible classroom design, and positive behavior support. Limitations include the single-site focus and a stronger emphasis on teacher perspectives than student voices. Future research should examine inclusive classroom management across diverse school contexts and include student perspectives more extensively.